2014
DOI: 10.1073/pnas.1404845111
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of three unique Dehalococcoides that respire on persistent polychlorinated biphenyls

Abstract: Fastidious anaerobic bacteria play critical roles in environmental bioremediation of halogenated compounds. However, their characterization and application have been largely impeded by difficulties in growing them in pure culture. Thus far, no pure culture has been reported to respire on the notorious polychlorinated biphenyls (PCBs), and functional genes responsible for PCB detoxification remain unknown due to the extremely slow growth of PCB-respiring bacteria. Here we report the successful isolation and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
183
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(196 citation statements)
references
References 23 publications
(32 reference statements)
3
183
0
Order By: Relevance
“…(Bedard, 2008), Bacterium o-17 (Cutter et al, 1998) and Dehalobium chlorocoercia DF-1 (Wu et al, 2002) were shown to be involved in the reductive dechlorination of PCB congeners. The difficulty in cultivating PCB dechlorinators in pure culture impedes further characterization, optimization, and application in in-situ bioremediation (Wang et al, 2014). Recently, Wang et al used traditional culture techniques with tetrachloroethene as an alternative electron acceptor and successfully isolated and characterized three PCB-respiring Dehalococcoides mccartyi strains.…”
Section: Introductionmentioning
confidence: 99%
“…(Bedard, 2008), Bacterium o-17 (Cutter et al, 1998) and Dehalobium chlorocoercia DF-1 (Wu et al, 2002) were shown to be involved in the reductive dechlorination of PCB congeners. The difficulty in cultivating PCB dechlorinators in pure culture impedes further characterization, optimization, and application in in-situ bioremediation (Wang et al, 2014). Recently, Wang et al used traditional culture techniques with tetrachloroethene as an alternative electron acceptor and successfully isolated and characterized three PCB-respiring Dehalococcoides mccartyi strains.…”
Section: Introductionmentioning
confidence: 99%
“…This gene cluster is conserved in sequence (Ն98% identity) and synteny in three other D. mccartyi strains, DCMB5, GT, and CG5 (7,23,24). Transcription of the rdhA gene (cbdbA1453) was shown previously to be upregulated in the presence of 1,2,3-trichlorobenzene (TCB) (25).…”
mentioning
confidence: 99%
“…The genomes of D. mccartyi strains contain between 11 and 36 nonidentical rdhAB genes encoding the catalytic subunit A and the putative membrane anchor B of reductive dehalogenase homologous (Rdh) proteins, respectively, (3)(4)(5)(6)(7). This high number probably reflects the diversity of organohalogen compounds, which can be reductively dehalogenated by Dehalococcoides strains.…”
mentioning
confidence: 99%
“…Recently, more strains from this species were isolated including strain JNA [85,86], CG1 [87,88], CG4 [87,88], CG5 [87,88], SG1 [87,88], AD14-1 [89] and AD14-2 [89].…”
Section: Dehalococcoidesmentioning
confidence: 99%
“…Sand and silt near Liangjiang River 2014 [87,88] Dehalococcoides mccartyi CG4 Sand and silt of ditch sediment near electronic waste dump site 2014 [87,88] Dehalococcoides mccartyi CG5 Sand and silt of ditch sediment near electronic waste dump site 2014 [87,88] Dehalococcoides mccartyi SG1 Digester sludge of an industrial wastewater treatment plant 2014 [87,88] Dehalococcoides mccartyi AD14-1 An anaerobic digester in a wastewater treatment plant 2013 [89] Dehalococcoides mccartyi AD14-2 An anaerobic digester in a wastewater treatment plant 2013 [89] Dehalococcoides mccartyi MB [48,50,178,179] from pristine environments where naturally-occurring organohalides are believed to feed OHRB.…”
Section: Chaptermentioning
confidence: 99%